TRANSITION TO A NEW LEVEL OF PROFESSIONAL TRAINING OF COMPETITIVE DIRECTORS IN THE DIMENSION OF INTEGRATION INTO THE EUROPEAN EDUCATIONAL SPACE: CHANGING THE SPECIALTY FROM “STAGE ARTS” TO “PERFORMING ARTS” - Шумакова, Світлана (SWorldJournal, 2025)
In light of the trends of the global educational process and the European integration vector, a new level of professional training of competitive directors is being implemented, capable of meeting the modern challenges of the labor market and the artistic